Reinvestigation of the Late Devonian Lycopsid Sublepidodendron grabaui from Anhui Province, South China - Peng Xu; Le Liu; Deming Wang (Biology, 2022)
South China displays Devonian strata with well-exposed outcrops and is regarded as a diversity hotspot of Late Devonian lycopsids. The heterosporous lycopsid Sublepidodendron grabaui has been studied for over ten years, with its general morphology, aerial stem anatomy, microsporangiate strobili, and growth architecture reported. Based on new specimens from Guangde City, Anhui Province, this study provides further knowledge about the megasporangiate strobili and megaspores of S. grabaui. Its slender megasporangiate strobili occur singly or in pairs and occasionally bifurcate in the middle-upper portion. Each megasporophyll consists of a flattened pedicel and an adaxially curved lamina. The lamina forms a downturned heel at the base. Each sessile megasporangium contains at least eight Lagenicula-type megaspores with a small gula. The other observed characteristics of S. grabaui in this study conform to those previously known and are compared to relative coeval taxa.